Circular RNA hsa_circ_0000144 aggravates ovarian Cancer progression by regulating ELK3 via sponging miR-610 - Dandan Wu; Jia Liu; Liji Yu; Shaofang Wu; Xiaomei Qiu (BMC, 2022)
Abstract Background Ovarian cancer is a common cause of death among women and a health problem worldwide. Circ_0000144 has been confirmed to be an oncogene involved in cancer progression, such as gastric cancer. However, the role of circ_0000144 in ovarian cancer remains unclear and needs to be elucidated. This retrospective study aimed to investigate the underlying mechanism of circ_0000144 in ovarian cancer. Methods Differentially expressed circ_0000144 expression in ovarian cancer and normal tissues was identified by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). In vitro assays were performed to explore the biological functions of circ_0000144 in ovarian cancer cells. An in vivo xenograft model was used to investigate the efficacy of circ_0000144 in the progression of ovarian cancer. Results Circ_0000144 was significantly upregulated in ovarian cancer cells and tissues. Circ_0000144 overexpression significantly promoted ovarian cancer cell proliferation, migration, and invasion. This study further demonstrated that circ_0000144 downregulated ELK3 levels by sponging miR-610 in ovarian cancer cells. Moreover, circ_0000144 significantly promotes ovarian cancer tumorigenesis in vivo. Conclusion Our data indicate that circ_0000144 could enhance the carcinogenesis of ovarian cancer by specifically targeting miR-610, which may serve as a novel target for the diagnosis and prognosis of ovarian cancer.